Determination of Calcium Metal in Calcium Cored Wire - Dong Qiu, Hui; Han, Mei; Zhao, Bo; Xu, Gang; Xiong, Wei (Asian Journal of Chemistry, 2013)
The calcium analysis method in cored wire products is mainly measuring the total calcium content, including calcium oxide and calcium carbonate. According to the chemical composition of calcium cored wire and the chemical property of the active calcium in it, the gas volumetric method has been established for the determination of calcium content in calcium cored wire and a set of analysis device is also designed. Sampling in the air directly, intercepting the inner filling material of samples, reacting with water for 10 min, using standard comparison method and then the accurate calcium content can be available. The recovery rate of the experimental method was 93-100 %, the standard deviation is less than 0.4 %. The method is suitable for the determination the calcium in the calcium cored wire and containing active calcium fractions.